택지개발사업 조경설계공모 당선안과 조성 현장 비교를 통해 본 전통 재현의 양상 - 김현희; Hyun Hee Kim; 소현수; Hyun Su So (한국조경학회지, 2015)
본 연구는 전통 재현을 위한 합리적 계획 방향을 모색하고자 ‘의정부 민락 2지구 도시기반시설 조경설계공모(2008)’와 ‘화성 동탄 2지구 택지개발사업 1단계 조경기본 및 실시설계공모(2012)’ 당선안의 설계 도판과 조성 현장을 비교 분석하였다. 먼저 설계 도판에 제시된 텍스트와 평면도, 입단면도, 다이어그램, 사례이미지, 투시도를 분석하여 재현 대상과 재현경관, 재현 공간의 구성과 배치, 재현 시설물의 디자인과 식재 양상을 파악한 후 조성 현장을 고찰하였다. 연구의 결과는 다음과 같다. 첫째, 재현 대상과 재현 경관의 유형은 대상지의 향토 경관으로써 농업 경관, 전통마을의 생활공간, 전통 수(水)공간, 전통문화로 구분된다. 둘째, 재현 공간의 구성 및 배치와 관련하여 주변 토지이용과 지역문화유산이 고려된 전통테마 공간들을 구성하였으나 조성 시 일부는 근린공원에 요구되는 운동공간이나 편의시설공간으로 변경되었다. 셋째, 재현 시설물의 경우 방지원도(方池圓島), 정자, 화계는 현장에 도입되었으나 창의적으로 디자인된 시설물은 설치되지 않았다. 넷째, 전통 식재 기법은 마을숲, 방지 내 원도, 화계에 수목을 도입하는 것에 집중되었다. 다섯째, 전문 자료를 토대로 한 주제 선정과 실험적 시설물 디자인 제시 등 전통 재현 작업이 진일보한 측면을 파악할 수 있었다. 여섯째, 조성 시 실현 가능한 주제 선정, 정보 해석을 위한 전문성, 전통 시설물의 창의적 디자인 등 앞으로 이루어질 전통 재현작업에 요구되는 과제들을 짚어보았다. In order to search for the reasonable planning directions for representing traditional landscape, this study conducted the comparative analysis of the designs on the panels and their constructions from both winners of “The Landscape Design Competitions for City Infrastructure of Minlak(2) District in Uijeongbu” and “The Design Competition for Dongtan(2) District Land Development Phase 1”. The representing targets and views, the composition and placement of representing space, the design of representing facilities and landscape planting were examined based on the text, master plans, elevations and cross sections, diagrams, images, and perspective drawings proposed from the competition panels. Then, the landscape constructions were reviewed. The results are as follows: First, the types of the representing targets and views are the agricultural landscape, as the local landscape of target area, which are divided into the life space of a traditional village, the traditional water space, and the traditional culture. Second, as to the composition and placement of representing space, the traditional theme spaces are formulated considering the surrounding land use and the local cultural heritage. However, some spaces were changed to the exercise space or convenient facility spaces required in a neighborhood park. Third, in the case of the representing facilities, a round island in the square pond, a traditional pavilion and Hwagye(terraced flower bed) were made without the facilities designed creatively. Fourth, the application of traditional planting techniques was focused on planting trees in the village forest on an island in the square pond and on Hwagye. Fifth, the traditional representing work has gradually advanced with the selection of subject and experimental facility designs based on the professional references. Sixth, the choice of the realizable subject, the expertise for information analysis and the creative design of the traditional facility are required in the future.